Laparoscopic Radical Hysterectomy Combined with Neoadjuvant Chemotherapy for Cervical Cancer Patients Effectively Improves Immune Function. (14th September 2022) - Liu, Mo; Wang, Hongping; Du, Shengye; Li, Wenying; Xuan, Fei; Zhao, Yinghui; Li, Na
Abstract : Objective. To evaluate the clinical efficacy of neoadjuvant chemotherapy plus laparoscopic radical hysterectomy for cervical cancer and the effect on the immune function of patients. Methods. Between January 2021 and December 2021, 42 patients with cervical cancer diagnosed and treated at our hospital were recruited and randomly assigned at a 1 : 1 ratio to receive neoadjuvant chemotherapy plus open radical hysterectomy (control group) or neoadjuvant chemotherapy plus laparoscopic radical hysterectomy (treatment group) (study group). Outcome measures included surgical indices, clinical outcomes, and immunological function. Results . There were no significant differences in the operative time between the two groups (P > 0.05 ). Patients receiving laparoscopic surgery had significantly less intraoperative bleeding and shorter time lapse before postoperative anal exhaustion, time lapse before out-of-bed activities, and hospital stay versus patients receiving open surgery (P < 0.05 ). Laparoscopic surgery resulted in a significantly higher efficacy (90.48%) versus open surgery (57.14%) (P < 0.05 ). After treatment, patients in the study group showed lower levels of carcinoembryonic antigen (CEA), squamous cell carcinoma antigen (SCC-Ag), and cancer antigen (CA125) than those in the control group (P < 0.05 ). After treatment, patients given laparoscopic surgery showed significantly lower CD 3+, CD 4+, and CD 8+ levels and higher CD 4+ /CD 8+ levels versus those with open surgery (P < 0.05 ). The postoperative conditions of the two groups, including recatheterization, postoperative blood transfusion, and secondary anti-inflammation were not significantly different (P > 0.05 ). The study group showed a significantly lower incidence of complications (19.05%) than the control group (71.43%) (P < 0.05 ). Patients in the study group had a lower reoperation rate and a higher survival rate (0.00%, 95.24%) than those in the control group (19.05%, 66.67%) (P < 0.05 ). Conclusion. Neoadjuvant chemotherapy plus laparoscopic radical hysterectomy effectively improves clinical efficacy, lowers cancer marker levels, improves patients' immune function, reduces the risk of adverse events, and improves patients' prognosis with less intraoperative bleeding, less trauma, faster postoperative recovery, and shorter hospital stay for cervical cancer patients.